HIV-1 viral protein r: from structure to function - Fritz, Joëlle; Briant, Laurence; Mély, Yves; Bouaziz, Serge; Rocquigny, Hugues (Future virology, 2010)
The viral protein r (Vpr) of HIV-1 binds several host proteins leading to pleiotropic functions, such as G2/M cell cycle arrest, apoptosis induction and gene transactivation. Vpr is encapsidated through the Gag C-terminus into the nascent viral particles, suggesting that Vpr plays several important functions in the early stages of the viral lifecycle. In this regard, Vpr interacts with nucleic acids and membranes to facilitate the preintegration complex migration and incorporation into the nucleus of nondividing cells. Thus, Vpr has to recruit several host and viral factors to promote its functions during HIV-1 pathogenesis. This article focuses on its interacting partners by giving an overview of the functional outcome of the different Vpr complexes, as well as the structural determinants of Vpr required for its binding properties.